Essays on the representational and derivational nature of grammar : the diversity of Wh-constructions - Aoun, Joseph (Linguistic inquiry monographs ;, 2003)
This book can be read on two levels: as a novel empirical study of wh- interrogatives and relative constructions in a variety of languages and as a theoretical investigation of chain formation in grammar. The book is divided into two parts. Part I investigates the distribution and interpretation of multiple wh- interrogative constructions, focusing on the workings of Superiority. Part II investigates the structure and derivation of relative constructions. The main languages discussed are Lebanese, Arabic, Chinese, and English. The theoretical materials are in the generative grammar tradition.